Ultrasound-Guided Block of the Internal Branch of the Superior Laryngeal Nerve Reduces Postoperative Sore Throat Caused by Suspension Laryngoscopic Surgery: A Prospective Randomized Trial - Bao, Yin; Xiong, Jun; Wang, Huijun; Zhang, Yang; Zhong, Qi; Wang, Guyan (Frontiers in Surgery, 2022)
Objective Suspension laryngoscopy is commonly used in operative laryngology. Although it‘s efficient and minimally invasive, it can lead to postoperative sore throat and cough. Because of intensive stimulation by suspension laryngoscope, procedures must be implemented under general anesthesia. Blocking the internal branch of the superior laryngeal nerve (iSLNB) is useful in inhibiting the endotracheal intubation stress response. Thus, we evaluated the efficacy of ultrasound-guided block of iSLNB to improve postoperative complications. Methods A total of 64 patients were scheduled for elective laryngeal cancer resection, and suspension laryngoscopic surgery was performed under general anesthesia with iSLNB (group iSLNB, n=32) and without a block (group C, n=32). Patients in group iSLNB received ultrasound-guided iSLNB bilaterally (0.2% ropivacaine, 2 ml each side). The primary outcome measures were the incidence and severity of sore throat and cough assessed 0.5 h, 2 h, 6 h and 24 h after tracheal extubation. The secondary outcome measures were heart rate and mean arterial pressure on arrival in the operating room (T0), at endotracheal intubation (T1), upon insertion of the suspension laryngoscope (T2), 5 min after insertion (T3), at tracheal extubation (T4) and 5 min after extubation (T5). Blood glucose levels were measured at T0, T3 and T5. Results The incidence and severity of postoperative sore throat and cough in the iSLNB group were significantly reduced within 6 h after extubation compared with those in the control group, regardless of whether swallowing was present (P<0.05). Compared to the control group from T0 to T5, except at T0, the iSLNB group had significantly lower heart rate and mean arterial pressure (P<0.05). Compared to T0, at other time points, the heart rates in the control group were significantly increased (P<0.05), and the mean arterial pressures at other time points in the iSLNB group were significantly lower than those at T0 (P<0.05). The blood glucose levels at T3 and T5 in the iSLNB group were significantly reduced compared with those in the control group (P<0.05). Conclusion Ultrasound-guided iSLNB might effectively ameliorate postoperative complications secondary to suspension laryngoscopic surgery with endotracheal intubation under general anesthesia and improve hemodynamic stability.